The Influence of Brand Ambassador, Tagline, and Outlet Location on Purchase Decisions: The Mediating Role of Brand Image - Gunarianto; Ike Kusdyah Rachmawati; Yunus Handoko (Al-Qalam Institue, 2026)
This study examines the influence of brand ambassador, tagline, and outlet location on purchase decisions, with brand image as a mediating variable, using Malang Strudel as a tourism-based retail case. A quantitative explanatory design was employed using purposive sampling of consumers who had purchased Malang Strudel within the last six months and had prior exposure to brand promotions. Data were collected through structured questionnaires across six outlet clusters and analyzed using PLS-SEM (SmartPLS 4). The results indicate that brand ambassador (β = 0.611), tagline (β = 0.396), and outlet location (β = 0.336) significantly influence brand image. Brand image strongly affects purchase decisions (β = 0.472) and serves as a key mediating mechanism, with the strongest indirect effect observed in the brand ambassador pathway (β = 0.289). While brand ambassador and tagline retain significant direct effects on purchase decisions, outlet location exhibits only a marginal direct influence. These findings underscore the central role of brand image as a perceptual bridge that transforms communication cues into consumer behavior. The study extends brand equity theory by demonstrating that brand image functions as the primary conversion mechanism between symbolic branding cues and purchase decisions in tourism-based retail contexts.